(untitled) (Conferencea, 2024)
This article covers the history of the development of Uzbekistan’s irrigation system. Irrigation systems have played an important role in the development of the country’s economy and culture since ancient times. The article analyzes, in particular, the changes during the Soviet era and after independence. The major water projects implemented during the Soviet era and their environmental consequences are discussed, as well as the reforms implemented after independence and new water management strategies. The article also examines the main problems in the management of water resources in Uzbekistan today and ways to solve them.